Economic burden assessment for the management of asthma patients at Mexico’s National Institute for Respiratory Diseases - Maria del Carmen Cano Salas; José Luis Miguel Reyes; Karen Sánchez Trejo; Erika del Carmen López Estrada; Jorge Salas Hernández; Monserrat Evelia Arroyo Rojas; Mauricio Castañeda Valdivia; Monserrat Escobar Preciado; Silvia Guzmán Vázquez; Sergio Ricardo García-García; Herman Soto Molina (Revista Alergia México, 2024)
Background. In Mexico, asthma is one of the top twenty causes of disease with 254,713 new cases reported in 2019. According to Phase 3 of the International Study of Asthma and Allergies in Childhood, the prevalence of asthma ranged from 5 to 14% in 6 Mexican cities with varied geographic conditions. The burden of this disease impacts the health system in terms of direct costs through increased hospitalization and treatment costs; and indirect costs such as school and work absenteeism. Methods. A retrospective, longitudinal observational study comprised by data from 247 female asthma patients, annual direct costs were estimated including: visits, laboratory tests, pharmacological treatment and management of crisis or exacerbations, to determine the annal burden of the disease from an institutional perspective and according to Global Initiative for Asthma classification. Results. The average annual cost was $43,813.92, which increased in relation to the need of inhaled corticosteroids and long-acting beta agonists dosage increase. The average doctor’s appointment cost was $2,004.57, $982.82  for crisis management and $2,645.95 for laboratory testing. Pharmacological treatment represented the main economic burden with an annual average cost of $38,180.58. Conclusions. The present analysis shows the severity of asthma and auxiliary treatments like biologics were the main factors that increased direct attention costs. The results highlight a high economic burden for asthma within the context of the third level of care in Mexico’s public health system.